(untitled) (Annals of Medical Research, 2024)
Aim: Acute bronchiolitis is a clinical condition characterized by inflammation of the bronchioles, primarily caused by viral agents in children under two years of age. The cornerstone of treatment includes hydration and oxygenation, while patients should be closely monitored for potential complications. Our objective is to evaluate the impact of anemia on treatment outcomes in children diagnosed with acute bronchiolitis. Materials and Methods: Children aged 1-24 months diagnosed with mild or moderate acute bronchiolitis in a tertiary pediatric health and disease clinic were retrospectively included in the study. Demographic characteristics and bronchiolitis severity (mild/moderate) were recorded. Pre- and post-treatment clinical severity, respiratory rate, heart rate, oxygen saturation levels, and bronchiolitis clinical scores were analyzed. The clinical findings and treatment responses of anemic and non-anemic patients were compared. A p-value of <0.05 was considered statistically significant in all analyses. Results: A total of 85 patients with a median age of 5.4 months (52.9% male) were included in the study. Anemia was present in 25.9% of the patients. At admission, the respiratory rate (RR) was significantly lower in anemic patients compared to non-anemic patients (median 37 vs 41, p=0.003). No significant differences were observed between anemic and non-anemic groups for clinical respiratory scores (CRS) (median 4.7 vs 4.7, p=0.721), heart rate (HR) (median 135.6 vs 134.3, p=0.798), or oxygen saturation (SaO2) (median 93.1 vs 93.0, p=0.304) at admission. Post-treatment, both groups demonstrated significant improvements in CRS, HR, and SaO2 (p<0.05 for all). However, RR remained lower in the anemic group compared to the non-anemic group (median 32.1 vs 36, p=0.003). The overall change in CRS and other parameters between the anemic and non-anemic groups was not statistically significant (p>0.05). Conclusion: Mild anemia does not affect the response to treatment for hypoxia in children with mild to moderate acute bronchiolitis.